FACTORS AFFECTING BUSINESS PERFORMANCE THROUGH KNOWLEDGE COMPETENCE AS A MEDIATION VARIABLE - Clinton , Clinton; Ie, Mei (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to determine the effect of entrepreneurial orientation and market orientation on business performance through knowledge competence as a mediating variable in Sunter culinary entrepreneurs. This study uses a non-probability sampling technique with a purposive sampling technique. The sample criteria include respondents who are culinary entrepreneurs in Sunter, North Jakarta. Then, business actors who have been running their business for more than 1 year. So, in this study researchers used 100 respondents. This study was analyzed using SmartPLS version 3.3.9. The results of the study show that entrepreneurial orientation and market orientation have a positive and significant effect on business performance. Knowledge competency can mediate the effect of entrepreneurial orientation and market orientation positively and significantly on business performance. entrepreneurial orientation and market orientation have a positive and significant effect on knowledge competence.